PENGARUH PEMBERIAN REWARD TERHADAP HASIL BELAJAR SISWA PADA PELAJARAN MATEMATIKA KELAS IV SD DI SD NEGERI 101740 TANJUNG SELAMAT TAHUN PEMBELAJARAN 20182019 - SURBAKTI, AMELIA SEPTIANI (Jurnal Ilmiah Aquinas, 2019)
This study aims to determine the effect of giving rewards to student learning outcomes. This research was conducted at the Public Elementary School 101740 Tanjung Selamat in April 2019. The study sample consisted of 60 students. The method of this research is the Quasi experimental design method which in the design of this study there are two groups, namely, the experimental group and the control class. The instrument used to collect data is the multiple choice test. Hypothesis testing is done using the "t" test.The results of statistical calculations show that the ability of students to answer post-test questions by giving rewards is included in the good category with an average value of 79.75. While the ability of students to answer post-test questions without being given treatment, giving rewards is included in the category with an average value of 65.81. Furthermore hypothesis testing shows ð‘¡ð‘ð‘œð‘¢ð‘›ð‘¡ is 2,042 then consulted with ð‘¡ð‘¡ð‘Žð‘ð‘™ð‘’ at a significant level Î± = 0.05. with df 58 = 2,042 Because ð‘¡ð‘ð‘œð‘¢ð‘›ð‘¡ obtained is greater than ð‘¡ð‘¡ð‘Žð‘ð‘™ð‘’, that is, 6,174 > 2,042, it is evident that the null or (Ho) hypothesis is rejected and the alternative hypothesis (Ha) is accepted. So, it can be concluded that giving rewards has a significant effect on the learning outcomes of class IV students at SD Negeri 101740 Tanjung Selamat Learning Year 2018/2019. And Then, giving this reward is well used in the learning process, especially in fractions.